Segmented Polyurethane Elastomers with Mechanochromic and Self‐Strengthening Functions. (25th February 2021) - Seshimo, Kota; Sakai, Hio; Watabe, Takuma; Aoki, Daisuke; Sugita, Hajime; Mikami, Koichiro; Mao, Yuchen; Ishigami, Akira; Nishitsuji, Shotaro; Kurose, Takashi; Ito, Hiroshi; Otsuka, Hideyuki
Abstract: Mechanochromic elastomers that exhibit force‐induced cross‐linking reactions in the bulk state are introduced. The synthesis of segmented polyurethanes (SPUs) that contain difluorenylsuccinonitrile (DFSN) moieties in the main chain and methacryloyl groups in the side chains was carried out. DFSN was selected as the mechanophore because it dissociates under mechanical stimuli to form pink cyanofluorene (CF) radicals, which can also initiate the radical polymerization of methacrylate monomers. The obtained elastomers generated CF radicals and changed color by compression or extension; they also became insoluble due to the mechanically induced cross‐linking reactions. Additionally, an SPU containing diphenylmethane units also exhibited highly sensitive mechanofluorescence. To the best of our knowledge, this is the first report to demonstrate damage detection ability and changes in the mechanical properties of bulk elastomers induced by simple compression or extension. Abstract : Mechanochromic elastomers that exhibit force‐induced cross‐linking reactions in the bulk state are prepared to demonstrate damage detection ability by color change and fluorescence, and changes in the mechanical properties of bulk elastomers induced by simple compression or extension.